2014
DOI: 10.2478/pjvs-2014-0098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of macrogol administration on the quality of macroscopic images and transit time in canine capsule endoscopy

Abstract: The present experiment evaluated the quality of macroscopic images and the mean time of capsule passage through different sections of the gastrointestinal tract in dogs subjected to different preparation protocols before capsule endoscopy. In the first examination, the colonoscopy preparation protocol was applied, and in the second examination, the animals were administered macrogol. The study revealed that macrogol administration before capsule endoscopy significantly improved the quality of macroscopic image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…Indeed, the GET and SITT of the 2 control animals were also markedly disparate and overlapped with those observed in the clinical cases. Similarly, values were comparable to those obtained from 36 clinically healthy 6-to 7-month-old research beagles infected with various intestinal nematodes (mean GET 1.94 h, sd 1.40 h; SITT 1.15 h, sd 1.01 h; A. C. Y. Lee, unpublished data) and those published in a recent study on healthy dogs 20 to 26 kg (Rychlik et al . 2014 ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Indeed, the GET and SITT of the 2 control animals were also markedly disparate and overlapped with those observed in the clinical cases. Similarly, values were comparable to those obtained from 36 clinically healthy 6-to 7-month-old research beagles infected with various intestinal nematodes (mean GET 1.94 h, sd 1.40 h; SITT 1.15 h, sd 1.01 h; A. C. Y. Lee, unpublished data) and those published in a recent study on healthy dogs 20 to 26 kg (Rychlik et al . 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, values were comparable to those obtained from 36 clinically healthy 6‐ to 7‐month‐old research beagles infected with various intestinal nematodes (mean GET 1.94 h, sd 1.40 h; SITT 1.15 h, sd 1.01 h; A. C. Y. Lee, unpublished data) and those published in a recent study on healthy dogs 20 to 26 kg (Rychlik et al . ). Finally, several patients had varying degrees of systemic illness (such as DIC, systemic lupus erythematosus, immune‐mediated thrombocytopenia), and the effect of these diseases on GI transit time is uncertain, particularly as studies in humans have shown increased transit times in critically ill trauma patients (Rauch et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations